Transportation management with SAP TM 9.0 : a hands-on guide to configuring, implementing, and optimizing SAP TM - Daithankar, Jayant (Apress, 2014)
The implementation of a TMS solution is a highly complex and mission critical project. If executed correctly a good TMS can deliver a number of benefits to the organization in terms of optimization, greater efficiency, reduced errors and improved revenue through accurate invoicing. However a number of projects fail to realize these benefits for a host of reasons such as an incorrect product selection, over customization of the system and lack of detailed processes. The evaluation and selection of the right transportation management system  is a very critical step in the successful implementation of a TMS product as well as ensuring that the organization is able to realize the benefits expected from the system. Transportation Management with SAP TM 9 is a guide for CIO/CXOs evaluating options for various transportation management solutions available in the market and helps inappropriate decision making before committing investment. A proven evaluation framework and guidance provided in the book can help decision makers with product selection and help to create a business case for management approval and design a future roadmap for the organization. The book provides a comprehensive understanding of what SAP transportation management is and is useful for teams involved in TM Implementation and roll outs to ensure preparedness. The book explains end-to-end freight life cycle processes, functional system landscape, implementation challenges and post go-live precautions required to optimize investments in SAP TM. Transportation Management with SAP TM 9 also acts as a step by step implementation guide with details of configuration required to set up a TM9 system. This book also covers the upgrade of SAP TM8 to SAP TM9 which will be useful for existing clients who are on TM 8. Nonavailability of SAP TM skilled resources is a major challenge faced by organizations and the book provides a detailed competency building plan along with skill set requirements to create a competent and trained workforce to manage-transformation.The current book available in the market on SAP TM is  based on  Version 6 release  which does not cover air freight processes. Our book covers end-to-end  air freight configuration scenarios for logistic companies.